2011
DOI: 10.1186/1752-1947-5-271
|View full text |Cite
|
Sign up to set email alerts
|

Primary extra-cranial meningioma in the right submandibular region of an 18-year-old woman: a case report

Abstract: IntroductionExtra-cranial meningioma or ectopic meningioma is a rare tumor. This tumor has been reported in various anatomic sites in the head and neck, mediastinum, skin and soft tissues. We report a rare case of ectopic meningioma in the submandibular region detected by using fine-needle aspiration cytology, histopathology and immunohistochemistry. This case represents another unusual site for extra-cranial meningioma, which prompted us to report it.Case presentationAn 18-year-old Dravidian woman presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 9 publications
2
25
0
3
Order By: Relevance
“…To date, the cytomorphology of extracranial meningiomas has been reported predominantly via case reports in the literature [9,10,11,12,13,14,15,16,17,19,20,21,23,24,25,26,27,28]. To the best of our knowledge, this study represents the largest series detailing the cytomorphology of such tumors.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…To date, the cytomorphology of extracranial meningiomas has been reported predominantly via case reports in the literature [9,10,11,12,13,14,15,16,17,19,20,21,23,24,25,26,27,28]. To the best of our knowledge, this study represents the largest series detailing the cytomorphology of such tumors.…”
Section: Discussionmentioning
confidence: 95%
“…Previously published case reports of metastatic and primary ectopic meningiomas described tumors with typical low-grade cytomorphology [9,10,11,12,13,14,15,16,17,19,20,21,23,24,25,26,27,28]. In our study most cytology samples, particularly those from ectopic tumors, also revealed typical morphological features characteristic of low-grade intracranial meningiomas such as spindle-shaped tumor cells, whorls (concentric spheres of tumors cells), intranuclear pseudoinclusions, nuclear grooves and psammoma bodies [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 It is believed that the arachnoid cells along the peripheral nerves are responsible for the origin in these cases. 3 In the following section, we describe the hospital course of a patient who presented with an extracranial meningioma involving the sphenoid sinus.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, recently, good result was reported to be achieved without antifungal treatment for noninvasive aspergillosis. 13 Historically, patients with aspergillosis infection have been treated with amphotericin B or combined therapy with amphotericin B and flucytosine or itraconazole.…”
mentioning
confidence: 99%